The Effect of Pesticides Usage Behaviour on General Health Conditions of Farmer in Jember Regency, Indonesia - Salim Salim; Erma Sulistyaningsih; Ristya Widi Endah Yani (Humanistic Network for Science and Technology (HNST), 2020)
The agricultural sector remains an important sector in Indonesia's economic development, and pesticides have been essential in agricultural practice to protect crops and increase crop production. However, pesticides can cause a negative impact on health as well as environmental. The purpose of this study was to determine the effect of pesticides usage behavior on farmers' general health conditions. This was an observational analytic study with cross sectional design. The respondent was 377 farmers selected by cluster sampling. The variable of knowledge, attitude and practice were analysed. Data analysis showed that there was a significant effect on the level of knowledge on the farmers' general health conditions with a p-value of 0.001. As much as 47.2% of respondents had a low level of knowledge about the use of pesticides. The attitude influenced the general health conditions of farmers with p-value of 0,000. As much as 52.5% of respondents had a positive attitude related to pesticides and 47.5% had a negative attitude concerning pesticides usage. The variable of practice on the use of pesticides significantly affected the general health conditions of farmers with a p-value of 0.003. And as much as 17.0% respondents showed a bad practice, 65.5% moderate practice and 17.5% good practice on pesticides. Keywords: attitude; health; knowledge; practice; pesticide